The weapon of blood: politics and intrigue at the decline of Akkad - Kraus, Nicholas (Zeitschrift für Assyriologie und vorderasiatische Archäologie, 2018)
By the end of the reign of Šar-kali-šarrī, the hegemony that Akkad held over southern Mesopotamia was weakening. The governors of Sumer began to assert their independence and break free from Akkad’s control, and the Gutium presence posed a significant threat to Akkad’s power. The present article includes a copy, edition, and commentary of an unpublished Sargonic letter, specifically concerned with the political machinations occurring during this period of upheaval in the Late Akkadian period. Of particular interest are references to the governors of Umma and Adab, the ensi-ship of Gutium, and military action at Uruk. Additionally, the events detailed in this new letter closely parallel another letter from Girsu, suggesting that the two letters are synchronous correspondence. The new letter furthers our understanding of the intrigue amongst the political elite and the events leading to the end of Akkadian supremacy in Sumer.